KINETIC CHANGES OF KIDNEY FUNCTION TESTS AMONG PATIENTSWITH KIDNEY FAILURE IN ROYAL MEDICAL SERVICES - Mais Elian Al-Abdallat; Maisan Mahmoud Hayajneh; Mai Mohammad Alfalahat; Sheraf Said Mufleh Almahawish; Esra Abed Ali Alshakhanbeh; Faten Thalji Al Mawajdeh; Jaafar Abu Abeele (European Scientific Journal, ESJ, 2015)
Introduction: Kidney function tests are requested to monitor the general status of kidney health in general, and particularly to assess renal failure status. Objectives: To investigate the efficacy of therapeutic options for renal failure patients through studying changes in selected laboratory investigations.. Methodology: A retrospective study design was involved to review files of patients with kidney failure at Royal Medical Services. A total of 263 files were reviewed for kidney function tests over a period of three months. After the end of data collection, data were analyzed employing SPSS V20. The representation of data was as means and standard deviations. Kinetic changes were tested using paired T-test. Significance between variables was considered at an alpha < 0.05. Results Among study variable including Hematocrit (HCT), mean cell volume (MVC), blood urea nitrogen (BUN), creatinine, phosphorous, calcium, albumin, sodium, and potassium, there were insignificant changes except for BUN (p=0.004), sodium (p=0.013), and potassium (p=0.000). Conclusion From the results, following changes in the level of kidney function tests help in assessment of renal failure status as the progression of disease can be monitored. Understanding and comparing various laboratory findings help in better monitoring of clinical status of patients.